2014
DOI: 10.1007/s00167-014-3252-6
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes in femoral tunnels after anatomic anterior cruciate ligament reconstruction

Abstract: Case series, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 53 publications
3
56
1
Order By: Relevance
“…16 Less encouragingly, the knee may be overconstrained initially, 17 and, when compared with single-bundle grafts, both double-bundle and triple-bundle grafts show inferior graft-tunnel healing on oblique coronal magnetic resonance images at 6 months postoperatively. 18 It has also been shown that during the first postoperative year, both of the femoral tunnels enlarge anteriorly and distally 19 and the most posterior tibial tunnel enlarges posterolaterally. 20 Shino's group have performed second-look arthroscopies, typically between 6 and 24 months postoperatively.…”
Section: See Related Article On Page 896mentioning
confidence: 99%
See 1 more Smart Citation
“…16 Less encouragingly, the knee may be overconstrained initially, 17 and, when compared with single-bundle grafts, both double-bundle and triple-bundle grafts show inferior graft-tunnel healing on oblique coronal magnetic resonance images at 6 months postoperatively. 18 It has also been shown that during the first postoperative year, both of the femoral tunnels enlarge anteriorly and distally 19 and the most posterior tibial tunnel enlarges posterolaterally. 20 Shino's group have performed second-look arthroscopies, typically between 6 and 24 months postoperatively.…”
Section: See Related Article On Page 896mentioning
confidence: 99%
“…21,22 They have reported that the morphology of triple-bundle grafts resembles that of the native ACL, but they have also noted incomplete synovial coverage of the graft, particularly of the posterolateral bundle, with complete or substantial rupture of 10% of the posterolateral bundles. 19 Recently Mae et al 22 have also reported that a triple-bundle hamstring tendon graft results in worse synovial coverage and more graft damage than a single-bundle bone-patellar tendon-bone graft. Moreover, at the femoral aperture they noted a space around 33% of their triple-bundle grafts but none of their single-bundle grafts.…”
Section: See Related Article On Page 896mentioning
confidence: 99%
“…The circumference of the tunnel was traced with a minimum of 15 reference points and the cross-sectional area was automatically calculated 32 . Tachibana et al determined the femoral tunnel crosssection area by measuring at three planes, perpendicular to the long axis, created at the aperture site, 5 and 10 mm from the aperture site on a 3D model 41 . Slice thickness used was 0.625 mm 41 .…”
Section: Radiographsmentioning
confidence: 99%
“…Tachibana et al determined the femoral tunnel crosssection area by measuring at three planes, perpendicular to the long axis, created at the aperture site, 5 and 10 mm from the aperture site on a 3D model 41 . Slice thickness used was 0.625 mm 41 . Robbrecht et al and Yang et al used axial CT images (0.625 mm thick) to segment and reconstruct the bone into a 3D model by a computer program; the femoral and tibial tunnels were separately analyzed by the program 31,47 .…”
Section: Radiographsmentioning
confidence: 99%
“…The HST graft is also a suitable alternative. While harvest graft site morbidity is lower with the HST, tendon-to-bone tunnel integration is less successful, as evidenced by postoperative femoral tunnel enlargement observed in second-look arthroscopy or CT [ 9 , 10 ] (Fig. 3 ).…”
Section: Graft Selectionmentioning
confidence: 99%